2004
DOI: 10.1079/pns2004343
|View full text |Cite
|
Sign up to set email alerts
|

Exercise signalling to glucose transport in skeletal muscle

Abstract: Contraction-induced glucose uptake in skeletal muscle is mediated by an insulin-independent mechanism that leads to translocation of the GLUT4 glucose transporter to the muscle surface membrane from an intracellular storage site. Although the signalling events that increase glucose transport in response to muscle contraction are not fully elucidated, the aim of the present review is to briefly present the current understanding of the molecular signalling mechanisms involved. Glucose uptake may be regulated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 41 publications
3
33
0
1
Order By: Relevance
“…Because p38 has been shown to play a stimulatory role in glucose uptake in skeletal muscles and adipocytes through expression of Glut4 (41)(42)(43)(44)(45)(46)(47)(48)(49), the blockade of p38 may reduce glucose uptake in theses tissues, resulting in excess glucose supply. The excess glucose is then converted into fatty acids and contributes to the development of hypertriglyceridemia and fatty liver.…”
Section: Discussionmentioning
confidence: 99%
“…Because p38 has been shown to play a stimulatory role in glucose uptake in skeletal muscles and adipocytes through expression of Glut4 (41)(42)(43)(44)(45)(46)(47)(48)(49), the blockade of p38 may reduce glucose uptake in theses tissues, resulting in excess glucose supply. The excess glucose is then converted into fatty acids and contributes to the development of hypertriglyceridemia and fatty liver.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the combination of AICAR and insulin promoted an additional glucose transport in muscle and neuronal cells (Shah et al 2011, Fediuc et al 2006, Hayashi et al 1998. However, the effect of AICAR on glucose uptake is lost when α2 or γ3 AMPK subunits are deficient (Barnes et al 2004, Jorgensen et al 2004, Mu et al 2001.…”
Section: Amp-activated Protein Kinase (Ampk)mentioning
confidence: 99%
“…Jorgensen et al 2004, studying soleus and EDL muscles of mice, showed that muscles of α1 or α2-AMPK knockout (KO) mice when stimulated by muscle contraction, present glucose uptake similar to wild-type mice. However, when stimulated by AICAR, only muscles of α1-AMPK KO mice showed glucose uptake levels preserved.…”
Section: Glucose Uptake Pathwaysmentioning
confidence: 99%
“…Together these second messengers activate a complex network of signaling events (353). Among all the protein kinases activated by contraction [e.g., PKA, PKC-␦ and -, extracellularly regulated protein kinases (ERK)-1 and -2, mitogen-activated protein kinase (MAPK), and Ca 2ϩ /calmodulin-dependent protein kinases (CaMK)], the activation of AMPactivated protein kinase (AMPK) is known to have a variety of metabolic actions (275,352), including the stimulation of fatty acid oxidation via the phosphorylation and inactivation of acyl-CoA carboxylase (ACC) and the consequent reduction in malonyl-CoA which releases the inhibitory effects on CPT-I (270, 400). In line with this, we have shown that AMPK plays a crucial role in the translocation of CD36 (73,277), and that of FABP pm (73).…”
Section: Contraction Signalingmentioning
confidence: 99%